Protein kinase A inhibition facilitates the antitumor activity of xanthohumol, a valosin‐containing protein inhibitor. Issue 4 (20th April 2017) - Shikata, Yuki; Yoshimaru, Tetsuro; Komatsu, Masato; Katoh, Hiroto; Sato, Reiko; Kanagaki, Shuhei; Okazaki, Yasumasa; Toyokuni, Shinya; Tashiro, Etsu; Ishikawa, Shumpei; Katagiri, Toyomasa; Imoto, Masaya
Abstract : Xanthohumol (XN), a simple prenylated chalcone, can be isolated from hops and has the potential to be a cancer chemopreventive agent against several human tumor cell lines. We previously identified valosin‐containing protein (VCP) as a target of XN; VCP can also play crucial roles in cancer progression and prognosis. Therefore, we investigated the molecular mechanisms governing the contribution of VCP to the antitumor activity of XN. Several human tumor cell lines were treated with XN to investigate which human tumor cell lines are sensitive to XN. Several cell lines exhibited high sensitivity to XN both in vitro and in vivo . shRNA screening and bioinformatics analysis identified that the inhibition of the adenylate cyclase (AC) pathway synergistically facilitated apoptosis induced by VCP inhibition. These results suggest that there is crosstalk between the AC pathway and VCP function, and targeting both VCP and the AC pathway is a potential chemotherapeutic strategy for a subset of tumor cells. Abstract : The inhibition of protein kinase A (PKA), a downstream kinase of adenylate cyclase (AC) pathway, enhanced the apoptosis‐inducing activity of xanthohumol (XN). It indicated that the AC/PKA pathway could contribute to preventing apoptosis induced by XN and that the activity of AC/PKA pathway in tumor cells could determine sensitivity to XN.